Higher perceived dominance in Toxoplasma infected men--a new evidence for role of increased level of testosterone in toxoplasmosis-associated changes in human behavior - Hodková, Hana; Kolbeková, Petra; Skallová, Anna; Lindová, Jitka; Flegr, Jaroslav (Neuro endocrinology letters, 2007)
Toxoplasma is parasite of cats that uses any warm-blooded animals as intermediate hosts. It is known to induce shifts in behavior, physiology and even morphology of its intermediate hosts, including humans. The lower second to fourth digit ratio (2D:4D ratio) in infected man and women, and higher height in infected man suggest that sex steroid hormones like testosterone could play a role in these shifts. Here, we searched for another indirect indication for a higher postnatal testosterone level, i.e. increased perceived dominance and masculinity in infected men. We showed portrait pictures of 89 male students of which 18 were Toxoplasma-infected to 109 female students. When we statistically corrected for age, men with latent toxoplasmosis were perceived as more dominant (p=0.009) and masculine (p=0.052). These results support the idea that the higher level of testosterone could be responsible for at least some of the toxoplasmosis-associated shifts in human and animal behavior.
Keywords: Male; Testosterone; Animals; percepce; chování; toxoplazmóza; Humans; testosteron; mužské pohlaví; Female; ženské pohlaví; Behavior; sociální dominance; Toxoplasma; Adult; zvířata; Toxoplasmosis; dospělí; lidé; Social Dominance; Perception